The Long-Term Effects of Alcohol on the Central Nervous System: Mechanisms, Cognitive Decline, and Associated Disorders - Matuszewska, Marcelina; Brzozowska, Monika; Wardal, Wiktoria; Furlepa, Natalia; Rzenno, Robert; Wojciechowska, Karolina; Wicha, Katarzyna; Sidz, Natalia; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Prolonged alcohol use exerts significant and multifaceted effects on the central nervous system (CNS). These effects are mediated by mechanisms such as oxidative stress, neuroinflammation, and disruptions in neurotransmission. Structural changes, including gray matter loss and hippocampal atrophy, underlie functional deficits such as memory impairment, cognitive decline, and emotional dysregulation. Chronic alcohol use also increases the risk of neurological conditions, including alcohol-induced dementia, Wernicke-Korsakoff syndrome, and other neurodegenerative diseases. This review synthesizes current findings and highlights the urgent need for longitudinal studies to better understand these impacts and guide intervention strategies.